Effects of BDNF Signaling on Anxiety-Related Behavior and Spatial Memory of Adolescent Rats in Different Length of Maternal Separation - Zhang, Xianqiang; Li, Haonan; Sun, Haoran; Jiang, Yinghong; Wang, Aihong; Kong, Yujia; Sun, Xiue; Zhu, Guohui; Li, Qi; Du, Zhongde; Sun, Hongwei; Sun, Lin (Frontiers in Psychiatry, 2020)
As an adverse form of early-life stress (ELS), maternal separation (MS) can interfere with the development of cognition and behaviors of adolescent rodents. Brain-derived neurotrophic factor (BDNF) is involved in the regulation of brain development and function, but the molecular mechanisms by which BDNF regulates brain function and behavior in MS with different stressor strengths remain unclear. This descriptive study characterized the levels of BDNF in the prefrontal cortex (PFC) and plasma corticosterone (CORT) from the offspring of rats exposed to early handling (EH, 15-min separation per day) and prolonged MS (PMS, 180-min separation per day), during postnatal days (PND) 1-21. The behavioral and biochemical analyses were performed during adolescence (PND 42-56). PMS resulted in reduced weight and decreased locomotor activity in the open field test and Y-maze task compared to control (CON) group, with EH showing an intermediate phenotype. BDNF protein levels in the PFC were lower in PMS compared to EH and further reduced in CON male rats. Plasma CORT levels were higher in PMS compared to CON with EH again showing intermediate levels. Neither PMS or EH affected spatial learning in the Y-maze task. These findings indicate that longer periods of maternal separation are necessary to increase anxiety-like behavior, elevate CORT levels, and further suppress BDNF levels in the PFC, providing a possible mechanism to explain why more severe forms of ELS lead to more significant psychiatric and medical consequences later in life.